A filter rod, a method of making the same and a filter

CN118575985BActive Publication Date: 2026-10-23HUBEI CHINA TOBACCO INDUSTRY CO LTD +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202410859234.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-28
Publication Date
2026-10-23
Estimated Expiration
2044-06-28

AI Technical Summary

Technical Problem

[0003]专利CN109588775A公开了一种具有降温功能的加热不燃烧卷烟滤棒,包括成型纸,以及包裹在成型纸内的复合滤棒,复合滤棒依次连接的耐高温中空棒、微孔降温滤棒和丝束滤棒,微孔降温滤棒中的纵向微孔间相互连通形成气流通道,可以提高降温材料的散热效果,对烟气进行有效降温,但结构和制造工序复杂,不易制备

Benefits of technology

[0101]1、本发明的滤棒拉伸强度高且具有优良的热稳定性,滤棒整体为多孔结构,烟气通过降温滤棒时,一方面,烟气可顺畅无阻碍地通过,另一方面,高温烟气与相变材料层的接触面积大,降温效率高,有利于获得良好的降温效果,提升吸食者的体验。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application provides a filter rod, which comprises the following raw materials in parts by weight: modified polylactic acid 78-83 parts, modified calcium carbonate 18-24 parts, stabilizer 1.5-2.5 parts, surfactant 1.5-2.5 parts and foaming agent 0.8-1.1 parts. Compared with the existing filter rod, the filter rod provided by the application has excellent heat resistance, large porosity, small suction resistance, good suction taste, uses environment-friendly degradable materials and does not pollute the environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of cigarette technology, and in particular to a filter rod, its preparation method, and a filter tip. Background Technology

[0002] Heated cigarettes typically reach temperatures exceeding 150℃ and are relatively short, resulting in excessively hot smoke upon inhalation. This leads to a significant difference in smoking experience and feel compared to traditional cigarettes. Furthermore, due to the high smoke temperature, traditional acetate fiber filter rods used in heated cigarettes exhibit noticeable collapse and softening. Therefore, selecting suitable cooling materials or improving the filter rod's composition is crucial for reducing smoke temperature and enhancing flavor.

[0003] Patent CN109588775A discloses a heated non-combustible cigarette filter rod with cooling function, including a forming paper and a composite filter rod wrapped inside the forming paper. The composite filter rod is sequentially connected to a high-temperature resistant hollow rod, a microporous cooling filter rod, and a fiber tow filter rod. The longitudinal micropores in the microporous cooling filter rod are interconnected to form airflow channels, which can improve the heat dissipation effect of the cooling material and effectively cool the smoke. However, the structure and manufacturing process are complex and difficult to prepare. Patent CN110506991A discloses a cooling filter rod, which is formed by solidifying cooling particles. The cooling particles mainly include a particle body and a phase change material layer covering the surface of the particle body. After being combined with a conventional filter rod, it can be directly used in cigarette production. The cooling effect can be controlled according to the amount of phase change material and cooling filter rod. The cooling efficiency is high. However, the phase change cooling material melts and leaks after contacting high-temperature smoke, resulting in high suction resistance.

[0004] Therefore, there is an urgent need for a biodegradable, high-temperature resistant filter tip that is simple in structure, easy to assemble, and meets the requirements for suction taste. Summary of the Invention

[0005] In view of this, the technical problem to be solved by the present invention is to provide a filter rod, wherein the filter tip made from the filter rod of the present invention can cool down, withstand high temperature, and will not soften when heated, thus satisfying the sucking taste, while being degradable and not polluting the environment.

[0006] This invention provides a filter rod comprising the following raw materials in parts by weight:

[0007] The mixture contains 78-83 parts of modified polylactic acid, 18-24 parts of modified calcium carbonate, 1.5-2.5 parts of stabilizer, 1.5-2.5 parts of surfactant, and 0.8-1.1 parts of foaming agent.

[0008] Preferably, the method for preparing the modified polylactic acid includes:

[0009] A) Pentaerythritol and tetraisopropyl titanate were added to acrylic acid, heated to react, washed and dried to obtain the intermediate;

[0010] B) Irradiate polylactic acid to obtain activated polylactic acid;

[0011] C) Add the intermediate and ferrous sulfate to deionized water and stir. Add activated polylactic acid, react, wash, and dry to obtain modified polylactic acid.

[0012] Preferably, the heating reaction in step A) is carried out at a temperature of 70–80°C for 1–2 hours.

[0013] The mass ratio of pentaerythritol to acrylic acid is (1.5–2):1;

[0014] In step B), the irradiation source is an electron accelerator, the irradiation temperature is 20–30°C, and the irradiation dose is 15 kGy–25 kGy.

[0015] Preferably, the mass ratio of the intermediate, ferrous sulfate, and activated polylactic acid in step C) is (3.5–4.5):(0.03–0.07):1;

[0016] The stirring time is 5 to 10 minutes; the reaction temperature is 60 to 70°C; and the reaction time is 5.8 to 6.2 hours.

[0017] Preferably, the method for preparing the modified calcium carbonate includes the following steps:

[0018] Modified calcium carbonate is obtained by mixing porous calcium carbonate and polyethylene glycol, heating under vacuum, and drying.

[0019] The heating temperature is 75-85℃, and the heating time is 1-2 hours; the drying temperature is 75-85℃.

[0020] Preferably, the stabilizer is epoxidized soybean oil; the surfactant is lecithin; and the foaming agent is azodicarbonamide.

[0021] Preferably, the method for preparing the porous calcium carbonate includes:

[0022] a1) Mix the polymaleic acid solution and the sodium carbonate solution to obtain the first solution;

[0023] The polymaleic acid solution and the calcium chloride solution were mixed to obtain the second solution;

[0024] a2) Add sodium polystyrene sulfonate to the first solution, stir, add the second solution, react, filter, wash, and dry to obtain porous calcium carbonate.

[0025] Preferably, the concentration of the sodium carbonate solution is 0.09–0.11 mol / L; the concentration of the calcium chloride is 0.09–0.11 mol / L; the concentration of the polymaleic acid solution is 1.2–1.8 g / L; and the concentration of the sodium polystyrene sulfonate is 3–4 g / L.

[0026] The reaction a2) is carried out at a temperature of 75–85°C for a time of 1.5–2.5 h.

[0027] The volume ratio of polymaleic acid solution to sodium carbonate solution in the first solution is 1:(1.9-2.1); the volume ratio of polymaleic acid solution to calcium chloride solution in the second solution is 1:(1.9-2.1).

[0028] This invention provides a method for preparing the filter rod according to any one of the above technical solutions, comprising the following steps:

[0029] S1) Modified polylactic acid, modified calcium carbonate, stabilizer, surfactant and foaming agent are mixed and ground to obtain a premix; the premix is ​​reacted to obtain a mixture;

[0030] S2) The mixture is added to the extruder and extruded. In the compression section of the extruder, supercritical CO2 is added to the system through the gas injection system. Finally, it is formed into a rod shape through the foaming die, cooled and granulated to obtain the filter rod.

[0031] The present invention provides a filter tip, comprising a hollow tube, a filter rod as described in the above-mentioned technical solution connected to the upper end of the hollow tube, and a forming paper wrapped around the surface of the hollow tube and the filter rod.

[0032] The present invention provides a cigarette, including the filter tip described in the above technical solution.

[0033] Compared with existing technologies, this invention provides a filter rod comprising the following raw materials in parts by weight: 78-83 parts modified polylactic acid, 18-24 parts modified calcium carbonate, 1.5-2.5 parts stabilizer, 1.5-2.5 parts surfactant, and 0.8-1.1 parts foaming agent. Compared with existing filter rods, the filter rod provided by this invention has excellent heat resistance, high porosity, low suction resistance, and a superior suction experience. It is made of environmentally friendly and biodegradable materials and does not pollute the environment. Detailed Implementation

[0034] This invention provides a filter rod, its preparation method, and a filter tip. Those skilled in the art can refer to the content of this document and appropriately modify the process parameters to achieve the desired results. It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art and fall within the scope of protection of this invention. The methods and applications of this invention have been described through preferred embodiments. Those skilled in the art can clearly modify or appropriately change and combine the methods and applications described herein without departing from the content, spirit, and scope of this invention to realize and apply the technology of this invention.

[0035] In this application, the term "and / or" describes the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, or B existing alone. A and B can be singular or plural.

[0036] In this application, "at least one" means one or more, and "more than one" means two or more. "At least one of the following" or similar expressions refer to any combination of these items, including any combination of single or multiple items.

[0037] This invention provides a filter rod comprising the following raw materials in parts by weight:

[0038] The mixture contains 78-83 parts of modified polylactic acid, 18-24 parts of modified calcium carbonate, 1.5-2.5 parts of stabilizer, 1.5-2.5 parts of surfactant, and 0.8-1.1 parts of foaming agent.

[0039] In one embodiment of the present invention, the filter rod comprises the following raw materials in parts by weight:

[0040] 80 parts modified polylactic acid, 20 parts modified calcium carbonate, 2 parts stabilizer, 2 parts surfactant and 1 part foaming agent.

[0041] In one embodiment of the present invention, the filter rod comprises the following raw materials in parts by weight:

[0042] The mixture contains 78 parts modified polylactic acid, 18 parts modified calcium carbonate, 1.5 parts stabilizer, 1.5 parts surfactant, and 0.8 parts foaming agent.

[0043] In one embodiment of the present invention, the filter rod comprises the following raw materials in parts by weight:

[0044] The mixture contains 83 parts modified polylactic acid, 24 parts modified calcium carbonate, 2.5 parts stabilizer, 2.5 parts surfactant, and 1.1 parts foaming agent.

[0045] The method for preparing the modified polylactic acid of the present invention includes:

[0046] A) Pentaerythritol and tetraisopropyl titanate were added to acrylic acid, heated to react, washed and dried to obtain the intermediate;

[0047] B) Irradiate polylactic acid to obtain activated polylactic acid;

[0048] C) Add the intermediate and ferrous sulfate to deionized water and stir. Add activated polylactic acid, react, wash, and dry to obtain modified polylactic acid.

[0049] The method for preparing modified polylactic acid according to the present invention first involves adding pentaerythritol and tetraisopropyl titanate to acrylic acid and reacting at 70–80°C for 1–2 hours. The mixture is then washed and dried to obtain an intermediate. The preferred reaction temperature is 72–78°C; more preferably 73–77°C; most preferably 74–76°C; particularly preferably 75°C; and the reaction time can be 1 hour, 1.5 hours, or 2 hours, or any value between these two.

[0050] According to the present invention, the mass ratio of pentaerythritol to acrylic acid is (1.5-2):1; specifically, it can be 1.5:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1, or 2:1.

[0051] In some specific embodiments, the mass ratio of pentaerythritol to acrylic acid is 1.7:1.

[0052] The mass ratio of pentaerythritol and tetraisopropyl titanate to acrylic acid provided by this invention is (1.5-1.9):(0.002-0.004):1.

[0053] Polylactic acid was irradiated to obtain activated polylactic acid.

[0054] The irradiation source is an electron accelerator, the irradiation temperature is 20-30°C, and the irradiation dose is 15kGy-25kGy; specifically, it can be 15kGy, 16kGy, 17kGy, 18kGy, 19kGy, 20kGy, 21kGy, 22kGy, 23kGy, 24kGy, or 25kGy.

[0055] Add the intermediate and ferrous sulfate to deionized water and stir for 5-10 minutes; then add activated polylactic acid and react.

[0056] According to the present invention, the mass ratio of the intermediate, ferrous sulfate and activated polylactic acid is (3.5-4.5):(0.03-0.07):1.

[0057] In some embodiments, the mass ratio of the intermediate, ferrous sulfate, and activated polylactic acid is (3.7–4.2):(0.04–0.06):1.

[0058] In one embodiment, the mass ratio of the intermediate, ferrous sulfate, and activated polylactic acid is 4:0.05:1.

[0059] The reaction temperature of this invention is 60-70°C, and the reaction time is 5.8-6.2 h; preferably, the reaction temperature is 62-68°C, and the reaction time is 5.9-6.1 h; more preferably, the reaction temperature is 65°C, and the reaction time is 6 h.

[0060] After the reaction, the mixture is centrifuged, washed, and dried to obtain modified polylactic acid. This invention does not limit the specific centrifugation, washing, and drying operations described above; those familiar with the process are acceptable.

[0061] Lactic acid is a crucial material in the production of cigarette filter rods. Polylactic acid (PLA) molecules contain abundant polar groups on their surface, exhibiting a strong affinity for polar substances. They can chemically react with tar components and low-molecular-weight substances, with the reactants remaining firmly on the fiber surface. Simultaneously, PLA foam materials possess a highly porous internal structure. Filter rods made from PLA foam materials, when assembled, offer low draw resistance and a superior smoking experience, leading to their increasing use in the cigarette industry. However, PLA has a low melting point and is prone to softening and melting under the heat of high-temperature smoke, eventually collapsing and sticking together. This damages the filter structure, increases draw resistance, and can even block airflow channels, negatively impacting the smoking experience.

[0062] The applicant has creatively discovered that the mechanical or heat resistance properties of polylactic acid (PLA) can be improved by grafting a second polymer segment or a special reactive functional group onto the molecular weight of PLA. This invention grafts pentaerythritol with acrylic acid to obtain a monomer containing four double bonds and an ester group. This monomer with four double bonds undergoes a grafting reaction with irradiated PLA. After irradiation, stable peroxides form on the PLA molecular chain. When the irradiated PLA is heated, these peroxides form large molecular free radicals of PLA, initiating the grafting polymerization of the monomer containing double bonds onto the PLA macromolecule, resulting in modified PLA. Furthermore, the ester group has good compatibility with PLA, increasing the reaction rate of the grafting reaction. Ferrous sulfate, as an auxiliary agent, prevents the monomer containing double bonds from undergoing self-polymerization, thus affecting the double bond grafting. The modified polylactic acid forms a stable network structure, with stronger intermolecular forces, which increases the glass transition temperature of polylactic acid and enhances its heat resistance. It is also less likely to soften and melt under high-temperature flue gas heating, thus preventing collapse.

[0063] The method for preparing modified calcium carbonate according to the present invention includes the following steps:

[0064] Modified calcium carbonate is obtained by mixing porous calcium carbonate and polyethylene glycol, heating under vacuum, and drying.

[0065] The preferred embodiment of the present invention is as follows: porous calcium carbonate is added to polyethylene glycol so that the polyethylene glycol can completely cover the surface of the porous calcium carbonate, and then the porous calcium carbonate covered with polyethylene glycol is placed in a vacuum drying oven for heating and then dried to obtain the product.

[0066] The heating temperature described in this invention is 75–85°C, and the heating time is 1–2 hours; the drying temperature is 75–85°C. The drying process is preferably performed using filter paper.

[0067] In some specific embodiments, the heating temperature is 77–82°C, the heating time is 1.1–1.8 h, and the drying temperature is 77–82°C.

[0068] In one specific embodiment, the heating temperature is 80°C, the heating time is 1.5 hours, and the drying temperature is 80°C.

[0069] According to the present invention, the method for preparing porous calcium carbonate includes:

[0070] a1) Mix the polymaleic acid solution and the sodium carbonate solution to obtain the first solution;

[0071] The polymaleic acid solution and the calcium chloride solution were mixed to obtain the second solution;

[0072] a2) Add sodium polystyrene sulfonate to the first solution, stir, add the second solution, react, filter, wash, and dry to obtain porous calcium carbonate.

[0073] The method for preparing porous calcium carbonate provided by the present invention first prepares 0.09-0.11 mol / L sodium carbonate solution, 0.09-0.11 mol / L calcium chloride solution, 1.2-1.8 g / L polymaleic acid solution, and 3-4 g / L sodium polystyrene sulfonate solution for later use.

[0074] Preferably, 0.1 mol / L sodium carbonate solution, 0.1 mol / L calcium chloride solution, 1.5 g / L polymaleic acid solution, and 3.5 g / L sodium polystyrene sulfonate solution are prepared for use.

[0075] A first solution is obtained by mixing a polymaleic acid solution and a sodium carbonate solution; a second solution is obtained by mixing a polymaleic acid solution and a calcium chloride solution.

[0076] The volume ratio of polymaleic acid solution to sodium carbonate solution in the first solution is 1:(1.9-2.1); the volume ratio of polymaleic acid solution to calcium chloride solution in the second solution is 1:(1.9-2.1). Preferably, the volume ratio of polymaleic acid solution to sodium carbonate solution in the first solution is 1:2; the volume ratio of polymaleic acid solution to calcium chloride solution in the second solution is 1:2.

[0077] Sodium polystyrene sulfonate is quickly poured into the first solution, stirred, and then the second solution is quickly added to initiate the reaction. The reaction temperature is 75–85°C, and the reaction time is 1.5–2.5 h. Preferably, the reaction temperature is 77–82°C, and the reaction time is 1.7–2.3 h. More preferably, the reaction is carried out at 80°C for 2 h.

[0078] After the reaction, the mixture is filtered, washed, and dried to obtain porous calcium carbonate. This invention does not limit the specific filtration, washing, and drying operations described above; those familiar with the process are acceptable.

[0079] Phase change materials (PCCs) absorb heat from the surrounding environment during phase transitions, leading to a decrease in ambient temperature and thus a cooling effect. However, solid-liquid PCCs exhibit fluidity in their liquid state, which can leak into the surrounding environment during heat storage and cooling processes. Their low thermal conductivity and slow response to temperature changes significantly limit their applications. This invention uses sodium carbonate and calcium chloride as carbon and calcium sources, respectively, and selects polymaleic acid as a surfactant and sodium polystyrene sulfonate as a crystal form regulator to prepare porous calcium carbonate with uniform particle size, high porosity, and good morphology. Polyethylene glycol (PEG), a PCC material, is loaded into the pores of the porous calcium carbonate via impregnation. This prevents PEG from leaking out after heating tobacco, while simultaneously increasing the contact area between the smoke and PEG, thus improving the cooling effect. Furthermore, calcium carbonate acts as a nucleating agent for polylactic acid (PLA), further improving the heat resistance of PLA.

[0080] In some embodiments, the stabilizer is epoxidized soybean oil.

[0081] In some embodiments, the surfactant is lecithin.

[0082] In some embodiments, the foaming agent is azodicarbonamide.

[0083] This invention provides a method for preparing the filter rod according to any one of the above technical solutions, comprising the following steps:

[0084] S1) Modified polylactic acid, modified calcium carbonate, stabilizer, surfactant and foaming agent are mixed and ground to obtain a premix; the premix is ​​reacted to obtain a mixture;

[0085] S2) The mixture is added to the extruder and extruded. In the compression section of the extruder, supercritical CO2 is added to the system through the gas injection system. Finally, it is formed into a rod shape through the foaming die, cooled and granulated to obtain the filter rod.

[0086] The filter rod preparation method provided by the present invention firstly involves mixing and grinding modified polylactic acid, modified calcium carbonate, stabilizer, surfactant and foaming agent to obtain a premix; the grinding time is 1 to 2 hours; it can be 1 hour, 1.5 hours or 2 hours.

[0087] The premix is ​​reacted to obtain a mixture; preferably, the premix is ​​added to a reaction vessel, the pressure is 6-7 MPa, the temperature is 93-98℃, the stirring speed is 440-460 r / min, and the reaction is carried out for 11-13 h to obtain a mixture.

[0088] In one embodiment, the pressure was 7 MPa, the temperature was 93°C, the stirring speed was 440 r / min, and the reaction time was 13 h.

[0089] In one embodiment, the pressure was 6 MPa, the temperature was 98°C, the stirring speed was 460 r / min, and the reaction time was 11 h.

[0090] In one embodiment, the pressure was 6.5 MPa, the temperature was 95°C, the stirring speed was 450 r / min, and the reaction time was 12 h.

[0091] The mixture is added to an extruder and extruded. The temperature of the first half of the extruder screw is 195℃~205℃, the temperature of the second half is 140℃~160℃, and the extrusion speed is 35~45r / min.

[0092] In one embodiment, the temperature of the first half of the zone is 200°C, the temperature of the second half of the zone is 150°C, and the extrusion speed is 40 r / min;

[0093] In one embodiment, the temperature of the first half of the zone is 195°C, the temperature of the second half of the zone is 160°C, and the extrusion speed is 35 r / min;

[0094] In one embodiment, the temperature in the first half of the zone is 205°C, the temperature in the second half of the zone is 140°C, and the extrusion speed is 45 r / min.

[0095] In the compression section of the extruder, supercritical CO2 is added to the system through the gas injection system at a flow rate of 8-12 L / min. Finally, it is formed into a rod shape through the foaming die, cooled and pelletized to obtain the filter rod.

[0096] The filter rod of this invention is prepared by foaming molding. The polylactic acid foam material has a high foaming ratio and large porosity. At the same time, the foaming molding process is not prone to breakage, has high tensile strength, and has excellent thermal stability. The filter rod has a porous structure. When flue gas passes through the cooling filter rod, on the one hand, the flue gas can pass through smoothly and without obstruction. On the other hand, the contact area between the high-temperature flue gas and the phase change material layer is large, resulting in high cooling efficiency. This is conducive to obtaining a good cooling effect and improving the user experience.

[0097] The present invention provides a filter tip, comprising a hollow tube, a filter rod as described in the above-mentioned technical solution connected to the upper end of the hollow tube, and a forming paper wrapped around the surface of the hollow tube and the filter rod.

[0098] This involves assembling a hollow tube and a filter rod, and then wrapping the surface with molded paper to obtain a filter nozzle. This invention does not limit the scope of the invention; any method known to those skilled in the art is acceptable.

[0099] The present invention provides a cigarette, including the filter tip described in the above technical solution.

[0100] Compared with the prior art, the present invention has the following beneficial effects:

[0101] 1. The filter rod of the present invention has high tensile strength and excellent thermal stability. The filter rod has a porous structure. When the smoke passes through the cooling filter rod, on the one hand, the smoke can pass through smoothly and without obstruction. On the other hand, the high temperature smoke has a large contact area with the phase change material layer, resulting in high cooling efficiency, which is conducive to obtaining a good cooling effect and improving the smoker's experience.

[0102] 2. In this invention, the modified polylactic acid forms a stable network structure, with stronger intermolecular forces, which increases the glass transition temperature of polylactic acid and enhances its heat resistance. It is also less likely to soften and melt under the heating of high-temperature flue gas, thus preventing collapse.

[0103] 3. In this invention, sodium carbonate and calcium chloride are used as carbon and calcium sources, respectively. Polymaleic acid is selected as a surfactant and sodium polystyrene sulfonate as a crystal form regulator to prepare porous calcium carbonate with uniform particle size, high porosity, and good morphology. Polyethylene glycol, a phase change material, is loaded into the pores of the porous calcium carbonate through an impregnation method to prevent polyethylene glycol phase change leakage. At the same time, it increases the contact area between flue gas and polyethylene glycol, thereby improving the cooling effect. In addition, calcium carbonate can act as a nucleating agent for polylactic acid, which improves the heat resistance of polylactic acid.

[0104] It should be understood that in the various embodiments of this application, the order of the above processes does not imply the order of execution. Some or all steps may be executed in parallel or sequentially. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of this application.

[0105] The numerical ranges and parameters involved in this invention have been presented as accurately as possible to the relevant values ​​in the specific embodiments. However, any numerical value inevitably contains standard deviations due to individual test methods. Therefore, unless otherwise expressly stated, it should be understood that all numerical ranges or specific data used in this disclosure may have a reasonable deviation within a certain range, for example, within 1% or 0.5%.

[0106] The embodiments and comparative examples of this invention describe some examples, in which the embodiments illustrate certain implementations of the invention. However, this does not mean that the effects of the invention can only be achieved in these examples.

[0107] To further illustrate the present invention, the following detailed description is provided in conjunction with embodiments.

[0108] Polylactic acid was purchased from Shanghai E. En Chemical Technology Co., Ltd., with a number-average molecular weight of 60,000.

[0109] Polymaleic acid was purchased from Pande (Shanghai) International Trading Co., Ltd., with a purity of 99%.

[0110] Sodium polystyrene sulfonate was purchased from Shanghai Yuanye Biotechnology Co., Ltd., with a number average molecular weight of 70,000.

[0111] PEG-600 was purchased from Haian Petrochemical Plant in Jiangsu Province;

[0112] Epoxidized soybean oil was purchased from Shandong Yunxin New Material Technology Co., Ltd.

[0113] Lecithin was purchased from Shanghai Borui Biotechnology Co., Ltd.

[0114] Preparation Example 1

[0115] The preparation method of modified polylactic acid-1 includes the following steps:

[0116] (1) Add 17g pentaerythritol and 0.03g tetraisopropyl titanate to 10g acrylic acid, react at 75℃ for 1.5h, wash and dry to obtain intermediate;

[0117] (2) 2g of polylactic acid was irradiated at 25°C using an electron accelerator with an irradiation dose of 20kGy to obtain activated polylactic acid;

[0118] (3) Add 4g of intermediate and 0.05g of ferrous sulfate to 50g of deionized water and stir for 10min. Then add 1g of activated polylactic acid and react at 65℃ for 6h. Centrifuge, wash and dry to obtain modified polylactic acid-1.

[0119] Preparation Example 2

[0120] The preparation method of modified polylactic acid-2 includes the following steps:

[0121] (1) Add 20g pentaerythritol and 0.03g tetraisopropyl titanate to 10g acrylic acid, react at 75℃ for 1.5h, wash and dry to obtain intermediate;

[0122] (2) 2g of polylactic acid was irradiated at 25°C using an electron accelerator with an irradiation dose of 20kGy to obtain activated polylactic acid;

[0123] (3) Add 4g of intermediate and 0.05g of ferrous sulfate to 50g of deionized water and stir for 10min. Then add 1g of activated polylactic acid and react at 65℃ for 6h. Centrifuge, wash and dry to obtain modified polylactic acid-2.

[0124] Preparation Example 3

[0125] The preparation method of modified polylactic acid-3 includes the following steps:

[0126] (1) Add 17g pentaerythritol and 0.03g tetraisopropyl titanate to 10g acrylic acid, react at 75℃ for 1.5h, wash and dry to obtain intermediate;

[0127] (2) Irradiate 2g of polylactic acid at 25°C with an electron accelerator and an irradiation dose of 30kGy to obtain activated polylactic acid;

[0128] (3) Add 4g of intermediate and 0.05g of ferrous sulfate to 50g of deionized water and stir for 10min. Then add 1g of activated polylactic acid and react at 65℃ for 6h. Centrifuge, wash and dry to obtain modified polylactic acid-3.

[0129] Preparation Example 4

[0130] The preparation method of porous calcium carbonate includes the following steps:

[0131] 1) Prepare 500ml of 0.1mol / L sodium carbonate solution, 0.1mol / L calcium chloride solution, 1.5g / L polymaleic acid solution, and 3.5g / L sodium polystyrene sulfonate solution for later use;

[0132] 2) Take two 200ml polymaleic acid solutions. Pour one 200ml polymaleic acid solution into 400ml sodium carbonate solution to obtain solution A. Pour the other 200ml polymaleic acid solution into 400ml calcium chloride solution and stir well to obtain solution B.

[0133] 3) Quickly pour 200ml of sodium polystyrene sulfonate solution into 200ml of solution A, stir well, and then quickly add 200ml of solution B. React at 80℃ for 2 hours, filter, wash, and dry to obtain porous calcium carbonate.

[0134] Preparation Example 5

[0135] The preparation method of modified calcium carbonate-A includes the following steps: take 5g of porous calcium carbonate and add 50g of PEG-600, then place it in a vacuum drying oven at 80℃ and heat for 1.5h. Place the sample on filter paper and dry at 80℃. Replace the filter paper every 30min to obtain modified calcium carbonate-A.

[0136] Preparation Example 6

[0137] The preparation method of modified calcium carbonate-B is the same as that of preparation example 5, except that porous calcium carbonate is replaced by calcium carbonate of equal mass.

[0138] Example 1

[0139] A biodegradable high-temperature resistant filter tip includes a hollow tube, a filter rod connected to the upper end of the hollow tube, and a molded paper wrapped around the surface of the hollow tube and the filter rod; the filter rod, by weight, contains the following raw materials: 80 parts of modified polylactic acid-1, 20 parts of modified calcium carbonate-A, 2 parts of epoxidized soybean oil, 2 parts of lecithin, and 1 part of azodicarbonamide.

[0140] The preparation method of the filter rod includes the following steps:

[0141] S1. Modified polylactic acid-1, modified calcium carbonate-A, epoxidized soybean oil, lecithin and azodicarbonamide are ground for 1.5 hours to obtain a premix.

[0142] S2. Add the premix to the autoclave, pressurize at 6.5 MPa, heat at 95°C, stir at 450 r / min, and react for 12 h to obtain the mixture.

[0143] S3. Add the mixture to the extruder and extrude it. The temperature of the first half of the extruder screw is 200℃ and the temperature of the second half is 150℃. The extrusion speed is 40r / min. In the compression section of the extruder, supercritical CO2 is added to the system through the gas injection system at a flow rate of 10L / min. Finally, the mixture is formed into a rod shape through the foaming die, cooled and granulated to obtain the filter rod.

[0144] The method for preparing the biodegradable high-temperature resistant filter tip in this embodiment includes the following steps: assembling a hollow tube and a filter rod, and wrapping the surface with molding paper to obtain the filter tip.

[0145] Example 2

[0146] A biodegradable high-temperature resistant filter tip includes a hollow tube, a filter rod connected to the upper end of the hollow tube, and a molded paper wrapped around the surface of the hollow tube and the filter rod. The filter rod, by weight, contains the following raw materials: 78 parts of modified polylactic acid-1, 18 parts of modified calcium carbonate-A, 1.5 parts of epoxidized soybean oil, 1.5 parts of lecithin, and 0.8 parts of azodicarbonamide.

[0147] The preparation method of the filter rod includes the following steps:

[0148] S1. Modified polylactic acid-1, modified calcium carbonate-A, epoxidized soybean oil, lecithin and azodicarbonamide are ground for 1 hour to obtain a premix.

[0149] S2. Add the premix to the autoclave, pressurize it at 6 MPa, temperature at 98℃, stir at 460 r / min, and react for 11 h to obtain the mixture.

[0150] S3. Add the mixture to the extruder and extrude it. The temperature of the first half of the extruder screw is 195℃ and the temperature of the second half is 160℃. The extrusion speed is 35r / min. In the compression section of the extruder, supercritical CO2 is added to the system through the gas injection system at a flow rate of 8L / min. Finally, the mixture is formed into a rod shape through the foaming die, cooled and granulated to obtain the filter rod.

[0151] The method for preparing the biodegradable high-temperature resistant filter tip in this embodiment includes the following steps: assembling a hollow tube and a filter rod, and wrapping the surface with molding paper to obtain the filter tip.

[0152] Example 3

[0153] A biodegradable high-temperature resistant filter tip includes a hollow tube, a filter rod connected to the upper end of the hollow tube, and a molded paper wrapped around the surface of the hollow tube and the filter rod. The filter rod, by weight, contains the following raw materials: 83 parts modified polylactic acid-1, 24 parts modified calcium carbonate-A, 2.5 parts epoxidized soybean oil, 2.5 parts lecithin, and 1.1 parts azodicarbonamide.

[0154] The preparation method of the filter rod includes the following steps:

[0155] S1. Modified polylactic acid-1, modified calcium carbonate-A, epoxidized soybean oil, lecithin and azodicarbonamide are ground for 1 hour to obtain a premix.

[0156] S2. Add the premix to the autoclave, pressurize it at 7MPa, temperature at 93℃, stir at 440r / min, and react for 13h to obtain the mixture.

[0157] S3. Add the mixture to the extruder and extrude it. The temperature of the first half of the extruder screw is 205℃ and the temperature of the second half is 140℃. The extrusion speed is 45r / min. In the compression section of the extruder, supercritical CO2 is added to the system through the gas injection system at a flow rate of 12L / min. Finally, the mixture is formed into a rod shape through the foaming die, cooled and granulated to obtain the filter rod.

[0158] The method for preparing the biodegradable high-temperature resistant filter tip in this embodiment includes the following steps: assembling a hollow tube and a filter rod, and wrapping the surface with molding paper to obtain the filter tip.

[0159] Example 4

[0160] This embodiment provides a biodegradable high-temperature resistant filter tip and its preparation method. The specific implementation method is the same as that in Embodiment 1, except that modified polylactic acid-1 is replaced by an equal mass of modified polylactic acid-2.

[0161] Example 5

[0162] This embodiment provides a biodegradable high-temperature resistant filter tip and its preparation method. The specific implementation method is the same as that in Embodiment 1, except that modified polylactic acid-1 is replaced by an equal mass of modified polylactic acid-3.

[0163] Example 6

[0164] This embodiment provides a biodegradable high-temperature resistant filter tip and its preparation method. The specific implementation method is the same as that in Embodiment 1, except that modified calcium carbonate-A is replaced by an equal mass of modified calcium carbonate-B.

[0165] Comparative Example 1

[0166] This comparative example provides a biodegradable high-temperature resistant filter tip and its preparation method. The specific implementation method is the same as that in Example 1, except that the modified polylactic acid-1 is replaced by an equal mass of polylactic acid.

[0167] Comparative Example 2

[0168] This comparative example provides a biodegradable high-temperature resistant filter tip and its preparation method. The specific implementation method is the same as in Example 1, except that the modified calcium carbonate-A is replaced by an equal mass of calcium carbonate.

[0169] Comparative Example 3

[0170] A biodegradable high-temperature resistant filter tip includes a hollow tube, a filter rod connected to the upper end of the hollow tube, and a molded paper wrapped around the surface of the hollow tube and the filter rod. The filter rod, by weight, contains the following raw materials: 80 parts modified polylactic acid-1, 10 parts porous calcium carbonate, 10 parts polyethylene glycol, 2 parts epoxidized soybean oil, 2 parts lecithin, and 1 part azodicarbonamide.

[0171] The preparation method of the filter rod includes the following steps:

[0172] S1. Modified polylactic acid-1, porous calcium carbonate, polyethylene glycol, epoxidized soybean oil, lecithin and azodicarbonamide are ground for 1.5 hours to obtain a premix.

[0173] S2. Add the premix to the autoclave, pressurize at 6.5 MPa, heat at 95°C, stir at 450 r / min, and react for 12 h to obtain the mixture.

[0174] S3. Add the mixture to the extruder and extrude it. The temperature of the first half of the extruder screw is 200℃ and the temperature of the second half is 150℃. The extrusion speed is 40r / min. In the compression section of the extruder, supercritical CO2 is added to the system through the gas injection system at a flow rate of 10L / min. Finally, the mixture is formed into a rod shape through the foaming die, cooled and granulated to obtain the filter rod.

[0175] The preparation method of the biodegradable high-temperature resistant filter tip in this comparative example includes the following steps: assembling a hollow tube and a filter rod, and wrapping the surface with molding paper to obtain the filter tip.

[0176] Performance testing:

[0177] 1. Heat resistance

[0178] The glass transition temperature and thermal decomposition temperature of the filter rods prepared in the examples and comparative examples were determined by differential scanning calorimetry and thermogravimetric analysis.

[0179] 2. Mechanical properties

[0180] The elongation at break and impact strength of the filter rods prepared in the examples and comparative examples were determined by tensile testing machine and cantilever beam impact testing machine. The tensile performance test was conducted in accordance with the standard GB / T1040.2-2006, and the impact performance test was conducted in accordance with the standard GB / T1843-200. The results were taken as the average value of 5 test strips.

[0181] 3. Cooling performance

[0182] The filters prepared in the examples and comparative examples were used in cigarettes. Smoking was simulated according to the cigarette smoking mode specified in the national standard YC / T29-1996. The temperature at the center position of the cigarette filter rod 2 mm away from the mouthpiece was detected by a K-type thermocouple temperature detector. The number of simulated smokings was 9, with an interval of 30 seconds between each smoking, and the highest temperature was recorded.

[0183] The test results are shown in Table 1.

[0184] Table 1

[0185]

[0186] Comparing the experimental data in Table 1 for Examples 1-3, it can be seen that changing the ratio of raw materials in the filter rod still results in filter tips with good heat resistance, mechanical properties, and cooling performance. Comparing Examples 1 and 4, it can be seen that replacing modified polylactic acid-1 with an equal mass of modified polylactic acid-2 reduces the heat resistance, mechanical properties, and cooling performance of the filter tip. Comparing Examples 1 and 5, it can be seen that replacing modified polylactic acid-1 with an equal mass of modified polylactic acid-3 reduces the heat resistance and mechanical properties of the filter tip. Comparing Examples 1 and 6, it can be seen that replacing modified calcium carbonate-A with an equal mass of modified calcium carbonate-B may cause leakage after the polyethylene glycol phase change, leading to the mixing of flue gas and polyethylene glycol. The reduced contact area of ​​the glycol leads to a decrease in cooling effect. A comparison of Example 1 and Comparative Example 1 shows that replacing the modified polylactic acid with an equal mass of polylactic acid may weaken intermolecular forces, lower the glass transition temperature of polylactic acid, and reduce its heat resistance. A comparison of Example 1 and Comparative Example 2 shows that replacing the modified calcium carbonate-A with an equal mass of calcium carbonate allows calcium carbonate to act as a nucleating agent, increasing the heat resistance of polylactic acid; however, the absence of polyethylene glycol results in a decrease in cooling performance. A comparison of Example 1 and Comparative Example 3 shows that while directly adding the phase change material polyethylene glycol can achieve a cooling effect, direct blending with polylactic acid leads to leakage after phase change, resulting in a decrease in the mechanical properties of the filter rod and affecting the cooling effect.

[0187] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A filter rod, characterized in that, The ingredients include the following parts by weight: 80 parts of modified polylactic acid-1, 20 parts of modified calcium carbonate-A, 2 parts of epoxidized soybean oil, 2 parts of lecithin and 1 part of azodicarbonamide; The method for preparing the modified polylactic acid includes: A) 17g pentaerythritol and 0.03g tetraisopropyl titanate were added to 10g acrylic acid and reacted at 75°C for 1.5h. After washing and drying, an intermediate containing multiple double bonds and ester groups was obtained. B) Irradiate 2g of polylactic acid at 25°C using an electron accelerator with an irradiation dose of 20kGy to obtain activated polylactic acid with stable peroxides formed on the molecular chain. C) Add 4g of the intermediate and 0.05g of ferrous sulfate to 50g of deionized water and stir for 10min. Then add 1g of the activated polylactic acid and react at 65℃ for 6h. Centrifuge, wash and dry to obtain the modified polylactic acid. The modified calcium carbonate is a composite material of porous calcium carbonate supported on polyethylene glycol. Its preparation method includes: taking 5g of the porous calcium carbonate and adding 50g of PEG-600, placing it in a vacuum drying oven at 80℃ and heating for 1.5h, then placing the sample on filter paper and drying at 80℃, and replacing the filter paper every 30min to obtain the modified calcium carbonate. The porous calcium carbonate is prepared by a method comprising the following steps: preparing 500 ml of 0.1 mol / L sodium carbonate solution, 500 ml of 0.1 mol / L calcium chloride solution, 1.5 g / L polymaleic acid solution, and 3.5 g / L sodium polystyrene sulfonate solution respectively; taking two 200 ml portions of polymaleic acid solution, pouring one 200 ml portion of polymaleic acid solution into 400 ml of sodium carbonate solution to obtain the first solution, and pouring the other 200 ml portion of polymaleic acid solution into 400 ml of calcium chloride solution to obtain the second solution; quickly pouring 200 ml of sodium polystyrene sulfonate solution into 200 ml of the first solution, stirring evenly, and then quickly adding 200 ml of the second solution, reacting at 80°C for 2 hours, filtering, washing, and drying to obtain the porous calcium carbonate.

2. A method for preparing the filter rod according to claim 1, characterized in that, Includes the following steps: S1. Modified polylactic acid-1, modified calcium carbonate-A, epoxidized soybean oil, lecithin and azodicarbonamide are ground for 1.5 hours to obtain a premix. S2. Add the premix to the autoclave, pressurize at 6.5 MPa, heat at 95°C, stir at 450 r / min, and react for 12 h to obtain the mixture. S3. Add the mixture to the extruder and extrude it. The temperature of the first half of the extruder screw is 200℃ and the temperature of the second half is 150℃. The extrusion speed is 40r / min. In the compression section of the extruder, supercritical CO2 is added to the system through the gas injection system at a flow rate of 10L / min. Finally, the mixture is formed into a rod shape through the foaming die, cooled and granulated to obtain the filter rod.

3. A filter tip, characterized in that, It includes a hollow tube, a filter rod as described in claim 1 connected to the upper end of the hollow tube, and a forming paper wrapped around the surface of the hollow tube and the filter rod.

4. A cigarette, characterized in that, Includes the filter tip as described in claim 3.

Citation Information

Patent Citations

  • Incombustible cigarette filter rod with cooling function

    CN109588775A

  • Cooling filter stick, application and cigarette

    CN110506991A

  • Polylactic acid filter stick paper element and manufacturing method thereof

    CN104532386A

  • Application method of calcium carbonate in reconstituted tobacco coating liquid by being taken as perfuming carrier

    CN105231480A

  • Hydrophilicity regulation and control method for degradable polylactic acid

    CN117050242A